Socio-economic inequalities in injury incidence in the Netherlands (Italian Journal of Public Health, 2006)
Background: Interventions to reduce socio-economic inequalities in injury incidence should be tailored tospecific priority areas that may be identified by descriptive studies. We aimed to provide an overview ofexisting socio-economic inequalities in injury incidence in the Netherlands and to assess the potentialinfluence of methodological choices on the relationships found.Methods: Self-reported medically treated injuries (all injuries versus fractures) were derived from a surveyamong a random sample of 59 063 persons. Injuries resulting in hospital admissions (all injuries versusfractures) were derived from a prospective cohort study of 18 810 participants, linked to the NationalHospital Discharge Register for a follow-up period of 7 years. Logistic regression was used to calculate theodds ratios of self-reported medically treated injuries and fractures by level of education, occupation andincome, and of hospital-admitted injuries by level of education and occupation.Results: Socio-economic inequalities in injury incidence in the Netherlands were dependent on the indicator ofnon-fatal injury incidence, indicator of socio-economic status (SES) and studied cause of injury. In the majorityof specific relations analyzed, injury risks were not or only moderately elevated in lower SES-classes. Analysesfocusing on injury with higher severity levels (admitted injuries and/or admitted fractures) revealed thesteepest SES gradient with odds ratios of injury of 1.5 or more of the lowest socio-economic (educational)groups compared to persons with higher SES (education). In hospital admitted traffic injuries, we found themost striking difference with a threefold higher risk in the lowest educational groups.Conclusion: Future descriptive research into socio-economic differences in injury incidence should includeall three core indicators of SES and separate analyses on the more severe injuries should be conducted.
Keywords: injury; socio-economic status; inequality; incidence